Lymphocyte proliferation responses in patients with pseudotumors following metal-on-metal hip resurfacing arthroplasty. - Kwon, Y; Thomas, P; Summer, B; Pandit, H; Taylor, A; Beard, D; Murray, D; Gill, H (2010)
Locally destructive soft tissue pseudotumor has been reported in patients following metal-on-metal hip resurfacing arthroplasty (MoMHRA). A delayed hypersensitivity reaction type IV to nickel (Ni), chromium (Cr), or cobalt (Co) has been suggested to play a role in its aetiology. The aim of this study was to investigate the incidence and level of metal-induced systemic hypersensitivity in patients with MoMHRA, both with and without pseudotumor by measuring lymphocyte proliferation responses to metals. A total of 92 patients were investigated: (1) MoMHRA patients with pseudotumors (nine female, one male); (2) MoMHRA patients without pseudotumors (30 female, 30 male); and (3) age-matched control subjects without metal implants (9 female, 13 male). The venous blood samples were collected for serum Ni, Co, and Cr ion level measurements and lymphocyte transformation tests (LTT). A higher incidence and level of enhanced lymphocyte reactivity only to Ni was found in patients with MoMHRA compared to the patients without MoM implants, reflecting exposure and immune reactivity. However, lymphocyte reactivity to Co, Cr, and Ni did not significantly differ in patients with pseudotumors compared to those patients without pseudotumors. This suggests that systemic hypersensitivity type IV reactions, as measured by lymphocyte proliferation response to these metals, may not be the dominant biological reaction involved in the occurrence of the soft tissue pseudotumors.